STRENGTHENING ENVIRONMENTAL CHARACTER THROUGH ADIWIYATA PROGRAM AT SDN SERANG 11 (PIONIR: JURNAL PENDIDIKAN, 2025)
This study aims to identify and analyze the strengthening of environmental awareness character at SDN Serang 11 through the implementation of the Adiwiyata Program. This program is designed to shape students' awareness and behavior towards the environment, as well as integrate sustainability values in daily activities at school. The method used in this research is descriptive qualitative, with data collection through observation, interviews, and documentation.The results show that the Adiwiyata Program has successfully increased student participation in various environmental activities, such as tree planting, waste management, and environmental education. Students show improvement in their knowledge and attitude towards the environment, which is reflected in their behavior at school and at home. In addition, the involvement of teachers and parents in the program also contributed significantly to the success of this initiative. Overall, strengthening the character of environmental care through the Adiwiyata Program at SDN Serang 11 not only increases students' environmental awareness, but also builds a more environmentally friendly school community. This research is expected to serve as a reference for other schools in implementing similar programs to support sustainable student character development.Keywords: Adiwiyata, Strengthening, Environmental Care
Keywords: Pendidikan